Teaching Maritime English for Safety Communication: Evidence from Vessel Traffic Service Operation - Nursyam, Nursyam; Bungin, Sarce Sampe; Tandung, Albertha Lolo; Tjahjanto, Rachmat (Universitas Lancang Kuning, 2025)
Effective use of Maritime English is essential for maintaining navigational safety and preventing communication failures in international waters, particularly within Vessel Traffic Service environments where real time decisions influence vessel movements and risk levels. Despite the global adoption of Standard Marine Communication Phrases as a safety protocol, there remains limited empirical evidence on how these phrases are enacted in authentic operational settings and how such practices inform the teaching of Maritime English. This study investigates the real-world application of Maritime English for safety communication at Benoa Vessel Traffic Service in Indonesia. Using a qualitative descriptive design, data were generated through analysis of five communication transcripts, eleven semi structured interviews with operators, and three days of field observations. Findings reveal selective adherence to standard phrases during routine procedures, frequent shifts to simplified English and code switching in complex multilingual situations, and pragmatic prioritization of clarity and time sensitive coordination over strict protocol. These patterns highlight gaps between prescribed language taught in training and communicative realities faced by operators. The study contributes empirical insight for refining Maritime English pedagogy by integrating authentic communication tasks, simulation of multilingual scenarios, and training for adaptive yet safety-oriented language practices. In a broader context, the findings reinforce the importance of aligning ESP curriculum design with real operational discourse to support global maritime safety and enhance English language preparedness among future maritime professionals.